(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Viral infections in pregnancy are major causes of maternal and fetal morbidity and mortality. Infections develop in the neonate transplacentally, perinatally or postnatally. Objective: To determine the frequency of cytomegalovirus and human herpesvirus-1antigens in product of conceptus tissues of pregnant women with spontaneous abortion and to study the association of the various socio-demographic and antenatal factors. Methods: Fifty (50) product of conceptus tissues samples were collected during the period from September 2013 till April 2014 from pregnant women with spontaneous abortion attended at Al-Batool Teaching Hospital for Maternity and Children in Baqubah city. All sociodemographic and antenatal characteristics such as age, education level, economic level, occupation, residence, gestational age, history of abortion and gravity were recorded. Human cytomegalovirus and human herpes virus-1 antigens were detected by immunohistochemistry technique in Department of Microbiology, College of Medicine, University of Diyala. Results: Among 50 formalin-fixed, paraffin embedded product of conceptus tissues blocks, the results showed that positivity frequency of human cytomegalovirus and human herpesvirus-1 antigens were 36% (18 out of 50) for each one. Patients age varied from (15-45) years with mean of 29.48 years. The highest rate of viral infection was diagnosed in the age 26-35 years. Multiple variables regarding frequencies of cytomegalovirus and human herpesvirus-1antigens simultaneously, was evaluated, and none of the variables had significant difference. Conclusion: Human cytomegalovirus and human herpesvirus-1 seems to play a significant role in first trimester pregnancy loss and its infection rate is comparable with that in the other countries, also pregnant women in Baqubah city may have the risk for acquiring viral infection during pregnancy and consequently adverse pregnancy outcomes. Keywords: Abortion, cytomegalovirus, human herpes virus, immunohistochemistry, pregnant women Citation: Areej A. Hussein, Sawsan T. Salman, Basim M. Khashman. Frequency of human cytomegalovirus and human herpesvirus-1 antigens in product of conceptus tissues of pregnant women with spontaneous abortion. Iraqi JMS. 2017; Vol. 15(1): 94-102. doi: 10.22578/IJMS.15.1.12